Matrix degradation enhances stress relaxation, regulating cell adhesion and spreading - Badri Narayanan Narasimhan; Stephanie I. Fraley (Proceedings of the National Academy of Sciences, 2025)
In native extracellular matrices (ECM), cells utilize matrix metalloproteinases (MMPs) to degrade and remodel their microenvironment. Accordingly, synthetic matrices have been engineered to permit MMP-mediated cleavage, facilitating cell spreading, migration, and interactions. However, the interplay between matrix degradability and mechanical properties remains underexplored. We hypothesized that MMP activity induces immediate mechanical alterations in the ECM, which are subsequently detected by cells. We observed that both fibrillar collagen and synthetic degradable matrices exhibit enhanced stress relaxation following MMP exposure. Cells responded to these variations in relaxation by modulating their spreading and focal adhesions. Furthermore, we demonstrated that stress relaxation and cell spreading can be precisely controlled through the rational design of matrix degradability. These findings establish a fundamental link between matrix degradability and stress relaxation, with potential implications for a broad spectrum of biological applications.